Feed the future aquaculture project: Draft quarterly progress report: January-March 2013 - WorldFish (WorldFish, 2013)
The Feed the Future Aquaculture project is a five year transformative investment in aquaculture focused on 20 southern districts in Barisal, Khulna and Dhaka divisions, Bangladesh, which started in October 2011. This report describes the achievements of FtF-Aquaculture project activities implemented during the 6th quarter (January to March 2013) along with cumulative progress on FtF indicators. Due to the seasonality of fish and shrimp production, which is out of sync with the project year, final harvesting of aquaculture production was completed in this quarter. The achievements summarized below relate to progress of project activities. Progress against the FtF indicators that were not reported on previously are now included in this report.